Semi-chemical pulping from kelempayan (neolamarcla-cadamba) / Siti Noorbaini Sarmin - Sarmin, Siti Noorbaini (2003)
This research is covered about the effect of different beating revolution by using PFI Mill towards the physical and mechanical properties of paper with similar consistency, 0.3 %. This study was carry out by using pulps from Semi-chemical, Neutral Sulphite Semi Chemical (NSSC) pulping method. The raw material is delignified from Light Hardwood Neolamarcia Cadamba, from Rubiaceae family or also known by the local name, Kelempayan. Different beating are starting from 5,000, 10,000, 15,000, 20,000 and 25,000 rpm. From the different beating, it shows 25,000 rpm produced a better properties of paper. The paper properties such like Tensile Strength, Tearing Resistance, Bursting Strength and Folding Endurance have been carry out. From the testing result, it shows Tensile Index 0.589 N/mg, Tearing Index 1.212 mN/m2g-1, Burst Index kPa m2g-1 and Bulk 3.229 cm3/g. From here, we can indicate the ability of Neolamarcia Cadamba to produced pulp for paper production for future prospects is higher.